Minutes of the 2021 Business Meeting of the Charles S. Peirce Society. (Transactions of the Charles S. Peirce Society)
STEP will ultimately consist of a standalone TEI editor and of a virtual STEP Platform workflow management coupled with a TEI online editor system. I [as approved on January 13, 2022] i The Annual General Meeting of the Charles S. Peirce Society was held virtually via zoom on January 8, 2021. On behalf of the staff of the Peirce Project, I want to express our enormous gratitude to the Peirce Society and to all steadfast supporters of the Peirce cause and the Project's mission. Dr. Govindarajan is currently busy designing the STEP workflow by modeling it closely on a prototype designed by De Tienne: STEP Workflow Monitor.